The General Principle of the Warburg Effect as a Possible Approach for Cancer Immunotherapy: The Regulatory Effect of Plant Extracts Could Change the Game - Donika Ivanova; Severina Semkova; Boncho Grigorov; Milena Tzanova; Ana Georgieva; Dancho Danchev; Biliana Nikolova; Zvezdelina Yaneva (Molecules)
The interpretation of the biochemistry of immune metabolism could be considered an attractive scientific field of biomedicine research. In this review, the role of glycolysis in macrophage polarization is discussed together with mitochondrial metabolism in cancer cells. In the first part, the focus is on the Warburg effect and redox metabolism during macrophage polarization, cancer development, and management of the immune response by the cancer cells. The second part addresses the possibility of impacts on the Warburg effect through targeting peroxisome proliferator-activated receptors (PPARs). This could be an activator of native immune responses. Because of the reported serious adverse effects of using synthetic ligands for PPARs in combination with chemotherapeutics, searches for less toxic and more active PPAR inhibitors, as well as blocking undesirable cellular PPAR-dependent processes, are in progress. On the other hand, recent research in modern immunotherapy has focused on the search for gentle immune-modulating natural compounds with harmless synergistic chemotherapeutic efficacy that can be used as an adjuvant. It is a well-known fact that the plant kingdom is a source of important therapeutic agents with multifaceted effectiveness. One of these is the known association with PPAR activities. In this regard, the secondary metabolites extracted from plants could change the game.